Burckhalter, David, Baja California Missions: In the Footsteps of the Padres. Foreword Bernard L. Fontana. Photographs David Burckhalter and Mina Sedgwick. Southwest Center Series, ed. Joseph C. Wilder. Tucson AZ: Arizona State University Press, 2013. Pp. xviii+ 162+ 113 illustrations. $24.95 paper - Cimadomo, Guido (My University, 2020)
The Northwestern border of the Spanish colonization of America was characterized during the Sixteenth Century by a wide unexplored territory and the lack of density of the American Native nomads, which difficulted the establishment of former new towns from where to organize the conquest and domination of Nueva España. Baja California was the extreme peripheral borderland far from the colonial centers of power, is nevertheless interesting for the model of settlement implemented there beginning in the Seventeenth Century by the Jesuits in their attempt to evangelize and civilize local inhabitants.. Soon the Jesuits’ activities were complemented with political functions, and their missions came to act as territorial control posts for the Spanish Crown. The extreme climatic and environmental conditions of the region, together with the profound ignorance of the geographical configuration of the peninsula, in fact defined the missions as the main venues for the Spanish colonial understanding of the territory. They were not only places to promote spiritual conquest, but also defensive outposts along the royal route from the mineral mines to the administrative centers, part of a larger network developed to extend the frontiers of New Spain. A great deal of research exists on the role of the Catholic Church in the colonization of the continent, including this region. A new publication about these mission settlements is, therefore, always anticipated with interest for the new focus it can offer. ...
Post-refereed, pre-print version, de acuerdo con Consent Form. Publicado en: Religion and the Arts 18:4(2014). 591-592.DOI: https://doi.org/10.1163/15685292-01804006
Keywords: Jesuítas - Misiones; Misiones españolas - S.XVII; California; Jesuit; 17th century; Missions; Siglo XVII